Rate and Timing Effects of Growth Regulating Herbicides Applications on Grain Sorghum (Sorghum bicolor) Growth and Yield - Thierry E. Besançon; Ranjit Riar; Ronnie W. Heiniger; Randy Weisz; Wesley J. Everman (Advances in Agriculture)
Dicamba and 2,4-D are among the most common and inexpensive herbicides used to control broadleaf weeds. However, different studies have pointed the risk of crop injury and grain sorghum yield reduction with postemergence applications of 2,4-D. No research data on grain sorghum response to 2,4-D or dicamba exists in the Southeastern United States. Consequently, a study was conducted to investigate crop growth and yield response to 2,4-D (100, 220, and 330 g acid equivalent ha−1) and dicamba (280 g acid equivalent ha−1) applied on 20 to 65 cm tall sorghum. Greater stunting resulted from 2,4-D applied at 330 g acid equivalent ha−1 or below 45 cm tall sorghum whereas lodging prevailed with 2,4-D at 330 g acid equivalent ha−1 and dicamba applied beyond 35 cm tall crop. Regardless of local environmental conditions, 2,4-D applied up to 35 cm tall did not negatively impact grain yield. There was a trend for yields to be somewhat lower when 2,4-D was applied on 45 or 55 cm tall sorghum whereas application on 65 cm tall sorghum systematically decreased yields. More caution should be taken with dicamba since yield reduction has been reported as early as applications made on 35 cm tall sorghum for a potentially dicamba sensitive cultivar.